PSIKOLOGI MANUSIA DALAM AL-QURAN DAN HADIST - Batubara, Elida Hapni; Fitri, Novita; Ardimen, Ardimen (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This article endeavors to delve into the intricacies of human psychology within the framework of the Quran and Hadith. The research methodology employed is a comprehensive library research approach, utilizing reputable sources such as books, journals, and pertinent prior research related to the predetermined theme. The research findings illuminate that the field of psychology delves into the very essence of the human soul, exploring various phenomena, processes, and contextual backgrounds. Viewing humans from the perspective of individual and social entities, encompassing the psychological (spiritual) and biological dimensions, they are perceived as entities harmonizing both material and spiritual components. Within the context of their relationship with the Divine, humans are esteemed as servants (makhluq) holding the highest position. The comprehension of human psychology in the Islamic perspective is elucidated through the conceptual exploration of Nafs, al-Aqlu, al-Qalbu, and ar-Ruh.